Molecular and Serological Findings in Sheep During Two Coxiella burnetii Outbreaks in Sicily (Southern Italy) - Valeria Blanda; Giuseppina Chiarenza; Ilenia Giacchino; Sergio Migliore; Santina Di Bella; Francesco La Russa; Valeria Vaglica; Rosalia D’Agostino; Francesca Arcuri; Carmela Sciacca; Marilena Alfano; Natalia Sciortino; et al. (Animals)
Q fever is a widespread zoonotic disease caused by the obligate intracellular bacterium Coxiella burnetii, primarily transmitted through the inhalation of contaminated aerosols. This study aimed to detect C. burnetii in two Sicilian sheep flocks, with no better defined reproductive disorders reported by the farmers. Blood, individual and bulk milk, ticks, and conjunctival swabs were collected from both flocks (A and B). Real-time and traditional PCRs were carried out to detect C. burnetii DNA and anti-C. burnetii antibodies were searched using an ELISA. In terms of Farm A, C. burnetii DNA was detected in 7.1% of blood samples, 20% of individual milk samples, bulk milk, 66.6% of conjunctival swabs, and in all the examined tick pools. Anti-C. burnetii antibodies were found in 77.0% of sera, 92.5% of individual milk samples, and bulk milk. In terms of Farm B, C. burnetii DNA was detected in 3.8% of blood samples, 39.4% of individual milk samples, bulk milk, 100% of conjunctival swabs, and in all tick pools; anti-C. burnetii antibodies were present in 53.6% of sera, 73.2% of milk samples, and in bulk milk. Our results highlight the high diffusion of C. burnetii in the two outbreaks, with widespread pathogen circulation, significant shedding in dairy products, and high environmental contamination, highlighting the need for enhanced surveillance and control measures in dairy sheep farms.